Predictors of Operative Intervention in Patients With Lactic Acidosis. Issue 3 (March 2022) - Bankhead-Kendall, Brittany; Slama, Eliza M.; Isanaka, Pavan; Braddock, Amy
Background: Lactate levels in clinical practice are often used as a quantitative indicator for the severity of hypoperfusion and the responsiveness to therapeutic interventions. In the hospital acute care setting, lactic acidosis combined with the appropriate clinical exam signs warrants surgical evaluation. The purpose of our study was to evaluate all surgical consults for lactic acidosis in a single community hospital to identify what cofactors were most often predictive of the need for surgical management and operative intervention. Materials and Methods: A retrospective chart review within a 5-year period was conducted on all consultations to general surgery in which patients additionally had lactic acidosis defined as >2mEq. Within this population, various subjective and objective parameters were evaluated. Final analysis compared these parameters between patients with lactic acidosis who underwent surgical intervention and those who did not require operative intervention. Results: Within the 5-year period, 432 patients met our criteria of a surgical consult placed for lactic acidosis. Final results from the highest quality statistical model showed significant variables as diffuse tenderness on physical exam ( P -value = .0010, Odds Ratio (OR) = 2.77) and focal tenderness on physical exam ( P -value = .0440, OR = 1.76). The presence of peritoneal signs ( P -value = .0521, OR = 2.02) resulted in operative intervention twice as often in patients with lactic acidosis. Discussion: To better appropriate health care costs, measures need to be taken to ensure resources are being utilized properly. In patients with lactic acidosis, one should go "back to the basics" with the physical examination to determine which patients truly need a surgical consultation.